2011
DOI: 10.1002/adfm.201101721
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembling, Bioinspired Wax Crystalline Surfaces with Time‐Dependent Wettability

Abstract: One of the most fascinating properties of materials in nature is the superhydrophobic and self‐cleaning capabilities of different plant surfaces. This is usually achieved by the hydrophobic cuticles that are made of cutin and contain wax crystals both within them and on their surfaces. Here, bioinspired n‐hexatriacontane wax films are deposited via thermal evaporation and it is shown that the surface evolves in time via self‐assembly. This leads to a dramatic change in the wetting properties with a transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 36 publications
2
48
0
Order By: Relevance
“…6,7 Other approaches to generating re-entry geometries that achieve omniphobicity were later demonstrated. [8][9][10] It was also shown that small liquid droplets can bounce off an extremely hot superhydrophobic surface reminiscent of the Leidenfrost effect, provided that the heat transfer between the solid and liquid is sufficient to generate a vapor layer, which can only occur when the temperature of the solid substrate T solid is significantly above the liquid's boiling point (T solid > 150°C for water).…”
mentioning
confidence: 99%
“…6,7 Other approaches to generating re-entry geometries that achieve omniphobicity were later demonstrated. [8][9][10] It was also shown that small liquid droplets can bounce off an extremely hot superhydrophobic surface reminiscent of the Leidenfrost effect, provided that the heat transfer between the solid and liquid is sufficient to generate a vapor layer, which can only occur when the temperature of the solid substrate T solid is significantly above the liquid's boiling point (T solid > 150°C for water).…”
mentioning
confidence: 99%
“…The wax was evaporated at a temperature (T) of 200 °C by applying pulses of an electric current. The temperature of wax evaporation was obtained from experimental study of Pechook and Pokroy (2012). The pressure in the chamber was 10 -4 mbar.…”
Section: Nanostructurementioning
confidence: 99%
“…The melting temperature of n-hexatriacontane is T = 76 °C, and the wax doesn´t decompose (Matacotta and Ottaviani 1995). Methods of wax evaporation were obtained from the studies of (Pechook a Pokroy 2012;Bhushan et al 2009). …”
Section: Nanostructurementioning
confidence: 99%
See 2 more Smart Citations